2017
DOI: 10.7717/peerj.4078
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary kriging vs inverse distance weighting: spatial interpolation of the sessile community of Madagascar reef, Gulf of Mexico

Abstract: Information about the distribution and abundance of the habitat-forming sessile organisms in marine ecosystems is of great importance for conservation and natural resource managers. Spatial interpolation methodologies can be useful to generate this information from in situ sampling points, especially in circumstances where remote sensing methodologies cannot be applied due to small-scale spatial variability of the natural communities and low light penetration in the water column. Interpolation methods are wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 88 publications
2
20
0
Order By: Relevance
“…Exploration of the spatial structure of sample points via the average nearest neighbor function revealed that the observed values (11.9 units) were smaller than those expected by a random dispersion (53.1 units), which generated a nearest neighbor ratio of 0.225 and indicated a clustering tendency. The global autocorrelation quantified through Moran's I covariance index equaled 0.923 (p = 0.000005 at a distance of 24.5 m), which indicated a very high positive spatial dependency and validated the appropriateness of performing IDW on tightly spaced samples over similar depths (Li & Heap, 2011;Zarco-Perello & Simões, 2017). Cross-validation analysis optimized the power value (a) for IDW interpolations by both maximining the regression function between expected and observed values and minimizing its root mean squared error (Table S6).…”
Section: Spatial Analysismentioning
confidence: 78%
“…Exploration of the spatial structure of sample points via the average nearest neighbor function revealed that the observed values (11.9 units) were smaller than those expected by a random dispersion (53.1 units), which generated a nearest neighbor ratio of 0.225 and indicated a clustering tendency. The global autocorrelation quantified through Moran's I covariance index equaled 0.923 (p = 0.000005 at a distance of 24.5 m), which indicated a very high positive spatial dependency and validated the appropriateness of performing IDW on tightly spaced samples over similar depths (Li & Heap, 2011;Zarco-Perello & Simões, 2017). Cross-validation analysis optimized the power value (a) for IDW interpolations by both maximining the regression function between expected and observed values and minimizing its root mean squared error (Table S6).…”
Section: Spatial Analysismentioning
confidence: 78%
“…Exploration of the spatial structure of sample points via the average nearest neighbor function revealed that the observed values (11.9 units) were smaller than those expected by a random dispersion (53.1 units), which generated a nearest neighbor ratio of 0.225 and indicated a clustering tendency. The global autocorrelation quantified through Moran's I covariance index equaled 0.923 (p=0.000005 at a distance of 24.5m), which indicated a very high positive spatial dependency and validated the appropriateness of performing IDW on tightly spaced samples over similar depths (Li & Heap, 2011;Zarco-Perello & Simões, 2017). Cross-validation analysis optimized the power value (α) for IDW interpolations by both maximining the regression function between expected and observed values and minimizing its root mean squared error (Table S6).…”
Section: Spatial Analysismentioning
confidence: 86%
“…spatial autocorrelation), and the local influence of points (weighted average) diminishes with distance. IDW has been used for mapping invasive plants (Roberts et al 2004) and to understand the distribution of coral reef sessile organisms, with a higher accuracy than more advanced geostatistical interpolation methods (Zarco-Perello & Simões 2017). Recently, Gomes et al (2018) found that Maxent SDMs models largely overlapped with abundance maps derived from using IDW based inventory plots for 227 hyper-dominant Amazonian tree species.…”
Section: Introductionmentioning
confidence: 99%